Commentary on differential impact of TIM-3 ligands on NK cell function - Rieneke van de Ven (Journal for ImmunoTherapy of Cancer)
T-cell immunoglobin and mucin-domain containing molecule 3 (TIM-3) is an immune checkpoint receptor and a target for immune checkpoint blockers (ICBs). Unfortunately in human patients the success rate of anti-TIM-3 ICB remains rather limited. Multiple immune cells express TIM-3 and their functioning is affected by receptor–ligand interactions. Four ligands of TIM-3 have been identified: high-mobility group protein B1, galectin-9, phosphatidylserine and carcinoembryonic antigen cell adhesions molecule 1. Wang et al investigated which of these ligands interact with TIM-3 on natural killer (NK) cells, impairing NK cytotoxicity and proliferation. They demonstrated that galectin-9 was able to inhibit NK cell cytotoxicity in a TIM-3-dependent manner, and to block NK cell proliferation through interaction with CD44 on NK cells. They also showed that in head and neck squamous cell carcinoma (HNSCC), a high TIM-3+NK cell transcriptional signature was linked to poor survival probability, specifically in HNSCC caused by human papillomavirus infection. This study enhances our understanding of why anti-TIM-3 ICB may not be so effective as monotherapy and provides leads toward rational design of combination strategies and patient selection.